Fermented Cyprinus carpio L. sausage - Arslan, A; Dinçoglu, AH; Gönülalan, Z (Tubitak Scientific & Technological Research Council Turkey, 2001)
This study was carried out to investigate the appropriateness of carp (Cyprinus carpio L.) meat in the making of fermented sausage. Carp were obtained from Keban Dam Lake. Four groups of sausages were produced. The first group was made from carp meat alone. the second from mixtures of 67% carp meat and 33% red meat, the third from mixture of 50% carp meat and 50% red meat and the fourth from mixtures of 33% carp meat and 67% red meat. Samples of sausage were analysed for sensory properties, and microbiological and chemical characteristics on day 1 of production and days 7, 15 and 30 of ripening. In sensory analyses, it was observed that the quality of sausage during conservation was medium on days 1 and 7 in group 1. The same group was found to be of good quality on days 15 and 30. Group II was of good quality during all periods. Group III was of medium quality on day 1 but good on other days. On the other hand, on days 1 and 7 group IV was of medium quality and on days 15 and 30 of good quality. In microbiological analyses, it was found that all groups contained coliform microorganisms on day 1. The numbers of coliform microorganisms were 1.0 x 10(2) cfu/g, 2.0 x 10(2) cfu/g, 3.0 x 10(2) cfu/g and 1.1 x 10(3) cfu/g in groups I, II, II and IV, respectively. Staphylococcus-micrococcus was detected as 1.4 x 10(4)-2.7 x 10(4) cfu/g in group I. 1.4 x 10(4)-8.0 x 10(4) cfu/g in group II. 1.2 x 10(4)-3.1 x 10(4) cfu/g in group III and 8.5 x 10(3)-2.3 x 10(4) cfu/g in group IV. The numbers of mould and yeast as cfu/g were 6.5 x 10(3)-3.9 x 10(4), 1.3 x 10(4)-7.7 x 10(4), 3.4 x 10(3)-6.3 x 104 and 1.3 x 10(4)-4.0 x 10(4) for groups I, II, III and IV, respectively. In the chemical analyses, moisture contents were 50.20%-38.02% in group I, 50.51-39.68% in group II, 51.58%-39.26% in group IH and 50.94%-39.45% in group IV. Fat contents were determined to be 26.25%-30.76%. 26.43%-29.92%. 24.02%-30.08% and 24.51%-30.10% in groups I, II, III and IV, respectively. Protein contents were 21.02%-29.53%, 21.63%-28.97%, 22.22%-28.34%and 23.54%-28.30% in groups I, II, III, and IV, respectively. Calcium levels were 33.82-37,26 mg/100 g in group I, 26.04-30.80 mg/100 g in group II, 22.16-25.52 mg/100 g in group III and 19.86-23.71 mg/100 g in group IV. Phosphorus levels were 84.56-87.42 mg/100 g, 77.12-79.93 mg/100 g, 74.75-77.14 mg/100 g and 72.22-75.11 mg/100 g in groups I, II, III and IV, respectively. pH values were 5.77-5.46 in group I, 5.71-5.50 in group II, 5.76-5.51 in group III and 5.80-5.58 in group IV. In conclusion, these results indicate that it is possible to produce high quality fermented sausage from carp meat using permitted food additives and good technology.
Keywords: fermented; sausage; carp